Penal Reforms, Penal Ideology, and Vagrants in Norway ca. 1900 - Ulvund, Frode (Bergen Journal of Criminal Law & Criminal Justice, 2015)
Prevention through Treatment or Incapacitation? The article discuss how Norway's Vagrancy Act (1900) was an integrated and central part of the legal reform project engineered primarily by Bernhard Getz, and which was crowned with Penal Code of 1902. Before the Vagrancy Act came to effect in 1907, the police could detain vagrants and alcoholics in workhouses for up to six months on discretion, and the main function was incapacitation and social renovation. The Vagrancy Act introduced legal procedures in the court system before similar detention. In the article, it is argued that though treatment was an important rhetorical argument when shaping and passing the Vagrancy Bill, the main purpose for reforming regulations towards vagrants and alcoholics was still to incapacitate and to render them harmless. Among the penal reforms, the Vagrancy Act thus represented continuity when it came to purpose and innovation when it came to procedural rules.